VERNACULAR VOCABULARY SUFFIXED WORD-FORMATION MODELS OF TEXTS OF THE TOBOLSK ABALAK MONASTERY AT THE SECOND HALF OF THE XVIII CENTURY - Vykhrystyuk, Margarita Stepanovna; Okmyanskaya, Anna Viktorovna (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2016)
The article is devoted to the analysis of suffixed word-formative models of vernacular shorthand business texts of the Tobolsk Abalak monastery of the second half of the XVIII century. Subject of research is word-formation models of shorthand business texts vernacular vocabulary of the Tobolsk Abalak monastery of the second half of the XVIII century. Objective: to carry out a primary stylistic analysis of popular-colloquial elements on the word-formation level. The novelty of this study is that the object of attention, being handwritten monuments stored in the local archive, that belong to the period of formation of the Russian national language, have never been studied before; the second focus of attention being word-formation oppositions of the vernacular type of language found in business writing of the ancient capital of Siberia. The methodological basis of the research was constituted by the principles of the scientific-research approach to the text, i.e. the systematicity and historicism. These principles determine the attitude to the text as a source of information of various levels in terms of the unity of content and form. Taking this into account, the following methods were used for the purposes of the study: purposive sampling, descriptive, comparative. As a result of the linguistic analysis a conclusion was made that genetical correlation of words with vernacular word-formation features, that was considered as a stylistic marker at the previous stages of the history of language, becomes neutralized in the monastic business writing of the XVIII century. Practical implications of the study results are determined by the ability to use them in further studying historical grammar and history of the records management in Russia, reading special courses on linguistic issues of local history, source studies, historical stylistics.